Performance Food: Promoting foods with a functional benefit in sports performance. Issue 4 (December 2013) - Reid, K.
Summary: The food choices and eating habits of athletes and sportspeople are influenced by their lifestyle, the practical considerations of their sports and the physiological demands of training and competition programmes. There is a growing interest in foods with a functional benefit in sports performance and in products and foods which can enhance recovery post‐exercise and therefore support a faster return to training. This paper provides an overview of the nutritional functions of foods and fluids of current scientific interest to athletes and sportspeople. Practical dietary strategies are provided to illustrate how emerging research can be translated into food ideas, which can enhance the functional benefits to their maximum potential within existing scientific recommendations to minimise reliance on unnecessary dietary supplements.